Efektivitas Penerapan Media Audio Visual dalam Kurikulum Merdeka Belajar untuk Meningkatkan Keterampilan Mendengar pada Mahasiswa PBA UIN Mataram - Zabrina, Nahwa; Suparmanto, Suparmanto; Lestari, Cindy; Umaeda, Hasti; Nada, Nisrina Qatrun (CV. Creative Tugu Pena, 2023)
In this study, there is a goal to be achieved, namely to determine the effectiveness of the implementation of audio-visual media in the independent learning curriculum to improve listening skills. The method used in this research is descriptive qualitative. Qualitative descriptive research is one of the types of qualitative research. Data collection techniques include observation, interviews, and documentation. The data analysis technique used is domain analysis obtained from participant observation, interviews, or descriptive observations found in field notes. Through this approach, the researcher creates a complex picture, examines words, detailed reports, and studies situations experienced.